2013
DOI: 10.1007/s00296-012-2658-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of OMERACT-RAMRIS scores and computer-aided dynamic magnetic resonance imaging findings of hand and wrist as a measure of activity in rheumatoid arthritis

Abstract: The purpose of this study was to compare the value of conventional magnetic resonance imaging (MRI) finding of rheumatoid arthritis (RA) and computer-aided dynamic MRI measurements in predicting the activity of disease. The activity of the disease in 40 RA patients was evaluated by the disease activity score in 28 joints (DAS28). The conventional MRI of the wrists of all patients were scored for bone edema, synovitis and erosions, according to the criteria of RA-MRI scoring system (RAMRIS) developed by Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…35 Several studies have suggested that DCE-MRI is a sensitive biomarker of inflammation, demonstrating good correlation with laboratory markers of active disease and treatment response. 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…35 Several studies have suggested that DCE-MRI is a sensitive biomarker of inflammation, demonstrating good correlation with laboratory markers of active disease and treatment response. 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…K trans and the rate of early enhancement) as opposed to static images obtained at the peak of contrast enhancement used for RAMRIS methodology [12] , [30] . Further, several studies have suggested that DCE-MRI is a more sensitive biomarker of joint inflammation than RAMRIS, demonstrating better correlation with clinical and laboratory markers of active disease and response to treatment [31] , [32] . Although RAMRIS and DCE-MRI correlate and are valid measures for detecting treatment change, they are not interchangeable and the more direct link between dynamic MRI and the pathophysiology of vascularity and joint inflammation may make it more suitable for the identification of blood gene expression markers of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast ratio is correlated with synovial volume, erosion, vascularity, capillary permeability and metabolic activity, and with bone marrow edema and erosion, indicating that rapid contrasting tissue is associated with erosive disease. [13][14][15][16] In this study, we aimed to evaluate the relationship between serum angiogenic factor levels and disease activity in patients with RA using both clinical and dynamic wrist MRI data.…”
mentioning
confidence: 99%